2005
DOI: 10.4049/jimmunol.174.12.8183
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Expression Is Increased in Asthmatic Airways and Correlates with Expression of Th2-Attracting Chemokines and Disease Severity

Abstract: Thymic stromal lymphopoietin (TSLP) is said to increase expression of chemokines attracting Th2 T cells. We hypothesized that asthma is characterized by elevated bronchial mucosal expression of TSLP and Th2-attracting, but not Th1-attracting, chemokines as compared with controls, with selective accumulation of cells bearing receptors for these chemokines. We used in situ hybridization and immunohistochemistry to examine the expression and cellular provenance of TSLP, Th2-attracting (thymus and activation-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
650
2
26

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 783 publications
(701 citation statements)
references
References 28 publications
23
650
2
26
Order By: Relevance
“…We now show that activated human CD4 ϩ T cells express TSLPR and that TSLP can rapidly activate Stat5 and induce expression of Stat5 target genes. The greater effect of TSLP on activated than on resting T cells correlates with its induction by inflammatory processes (14,15) and the activation-induced expression of TSLPR that we now show. The ability of TSLP to induce IL-2R␣ expression may explain the higher sensitivity of CD4 ϩ T cells to low doses of IL-2 in the presence of TSLP, and it is possible that such an increase might augment an immune response even in a setting of low TCR engagement.…”
Section: Tslp Elevates Sensitivity Of Cd4 ϩ T Cells To Low Dose Of Il-2mentioning
confidence: 81%
See 1 more Smart Citation
“…We now show that activated human CD4 ϩ T cells express TSLPR and that TSLP can rapidly activate Stat5 and induce expression of Stat5 target genes. The greater effect of TSLP on activated than on resting T cells correlates with its induction by inflammatory processes (14,15) and the activation-induced expression of TSLPR that we now show. The ability of TSLP to induce IL-2R␣ expression may explain the higher sensitivity of CD4 ϩ T cells to low doses of IL-2 in the presence of TSLP, and it is possible that such an increase might augment an immune response even in a setting of low TCR engagement.…”
Section: Tslp Elevates Sensitivity Of Cd4 ϩ T Cells To Low Dose Of Il-2mentioning
confidence: 81%
“…TSLP has been implicated in the development of asthma and atopic dermatitis (11)(12)(13)(14)(15). TSLPR KO mice have a defective lung inflammatory allergic response, but this is reversed by adoptive transfer of WT CD4 ϩ T cells (11).…”
mentioning
confidence: 99%
“…Based upon the observation that airway epithelium cells directly affected T cell activation, we decided to test candidate factors that had been shown previously to play an inhibitory role in airway or intestinal epithelial cells, including TGF-b, IL-10, TSLP and NO [ [21][22][23]. When analyzing BEAS-2B cells for transcription of known inhibitory mediators, we found that TGF-b transcripts were detectable at high levels (Fig.…”
Section: Tgf-b Contributes To the Inhibitory Effects Of Bronchial Epimentioning
confidence: 99%
“…For instance, transgenic mice expressing TSLP in keratinocytes or in lung epithelial cells have been shown to develop atopic dermatitis-or asthma-like inflammation in the skin or the lung, respectively, while TSLPR null mice failed to develop an inflammatory lung response to inhaled antigen [5][6][7]. In humans, TSLP has been shown to be expressed by keratinocytes in atopic dermatitis and by bronchial epithelial cells in asthmatic airways [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transgenic mice expressing TSLP in keratinocytes or in lung epithelial cells have been shown to develop atopic dermatitis-or asthma-like inflammation in the skin or the lung, respectively, while TSLPR null mice failed to develop an inflammatory lung response to inhaled antigen [5][6][7]. In humans, TSLP has been shown to be expressed by keratinocytes in atopic dermatitis and by bronchial epithelial cells in asthmatic airways [8,9].In contrast to the pro-allergic action of TSLP, regulation of TSLP expression in epithelial cells has not been fully elucidated. Previous studies suggest that TSLP expression in mouse keratinocytes is regulated by vitamin D and retinoic acid signaling [10] [17].…”
mentioning
confidence: 99%